Cyanobacterial blooms in oligotrophic lakes: Shifting the high‐nutrient paradigm. (19th July 2021) - Reinl, Kaitlin L.; Brookes, Justin D.; Carey, Cayelan C.; Harris, Ted D.; Ibelings, Bas W.; Morales‐Williams, Ana M.; De Senerpont Domis, Lisette N.; Atkins, Karen S.; Isles, Peter D. F.; Mesman, Jorrit P.; North, Rebecca L.; Rudstam, Lars G.; et al.
Abstract: Freshwater cyanobacterial blooms have become ubiquitous, posing major threats to ecological and public health. Decades of research have focused on understanding drivers of these blooms with a primary focus on eutrophic systems; however, cyanobacterial blooms also occur in oligotrophic systems, but have received far less attention, resulting in a gap in our understanding of cyanobacterial blooms overall. In this review, we explore evidence of cyanobacterial blooms in oligotrophic freshwater systems and provide explanations for those occurrences. We show that through their unique physiological adaptations, cyanobacteria are able to thrive under a wide range of environmental conditions, including low‐nutrient waterbodies. We contend that to fully understand cyanobacterial blooms, and thereby mitigate and manage them, we must expand our inquiries to consider systems along the trophic gradient, and not solely focus on eutrophic systems, thus shifting the high‐nutrient paradigm to a trophic‐gradient paradigm .